The Effect of Three Different Meditation Exercises on Hypertension: A Network Meta-Analysis. (26th April 2017) - Yang, Hongchang; Wu, Xueping; Wang, Min
Abstract : We aimed to use the pairwise and network meta-analysis to estimate the effects of different meditation exercises on the control of systolic blood pressure (SBP) and diastolic blood pressure (DBP). Randomized controlled trials (RCTs) were retrieved from PubMed and Embase up to June 2016, which are published in English and reported on meditation exercise for hypertensive patients. Risks of bias assessment of the included studies were assessed by Cochrane Collaboration Recommendations and network meta-analysis was performed by ADDIS. Mean difference (MD) and its 95% confidence interval (CI) were used as the effect size. A number of 19 RCTs were included in this study. Results of pairwise comparisons indicated that meditation exercise could significantly decrease the SBP and DBP, compared with other interventions (MD = −7.10, 95% CI: −10.82 to −3.39; MD = −4.02, 95% CI: −6.12 to −1.92). With good consistence and convergence, network meta-analysis showed that there were no significant differences between meditation and other interventions on SBP. For DBP, Qigong was significantly lower than "no intervention" (MD = −11.73, 95% CI: −19.85 to −3.69). Qigong may be the optimal exercise way in lowering SBP and DBP of hypertensive patients, but a detailed long-term clinical research should be needed in the future.